“Evaluación de tres dosis de microorganismos benéficos (trichoderma harzianum), para el control de enfermedades en el cultivo de brocoli híbrido (royal favor F-1), bajo condiciones agroecológicas en la provincia de Lamas” - Flores Armas, Jhon (2014)
This paper titled "Evaluation of three doses of beneficia! microorganisms (Trichoderma harzianum) for disease control in broccoli crop hybrid (Royal Favor F-1) under agro-ecological conditions in the province of Lamas" aimed to to determine the effect of beneficia! microorganism in disease control broccoli crop hybrid Royal Favor F-1, determine the most effective dose in crop production broccoli hybrid Royal Favor F-1, and perform economic analysis of treatments in study, for which tour treatments were evaluated: TO (no application), T1 (200 cc.ha-1.Application of Trichoderma harzianum), T2 (250 cc.ha-1 application of Trichoderma harzianum) and T3 (300 ce. ha-1.Application Trichoderma harzianum). The parameters evaluated were: percentage of surviving, plant height, diameter of the base of the stem, inflorescence weight, disease incidence, yield t ha-1, and finally an economic analysis of all the treatments was performed. The results indicate that the variable incidence of disease treatment TO (control) with an average percentage of 74,82% incidence of disease attack statistically outperformed the other treatments; likewise the fungus Alternaría was more influenced with a percentage average of 62,0%; and lower grade with 12,2% caused by Marssonina at TO statistically outperforming the averages obtained for the other treatments. And that scored highest yield (t ha-1 128321,6), net profit (SI .31690,98), and the highest percentage in return (465,67%) was the T3, then T2, T1 and TO obtained yields 113, 104.30 t.ha-1; 95584,00 t.ha-1 and 73744,00 t.ha-1 respectively and thus lower values of net income and rate of return. Keywords: beneficia! microorganism, hybrid, broccoli, incidence, yield.